Japanese words and their uses - Miura, Akira (Charles E. Tuttle, 1983)
Ideal for beginners and intermediate students, Japanese Words and Their Uses covers the proper application of 250 prevalent terms in the Japanese language, while seeking to eliminate mistakes commonly made by pupils at this level. In clear, straightforward language, Japanese language professor Akira Miura offers the stepping-stones of language acquisition, while incorporating more kanji into their learning. This is the definitive guide no student of Japanese should be without.